Flow Dynamic Analysis of Core Shooting Process through Experiment and Multiphase Modeling - Changjiang Ni; Gaochun Lu; Tao Jing; Junjiao Wu (Advances in Materials Science and Engineering)
Core shooting process is the most widely used technique to make sand cores and it plays an important role in the quality of sand cores as well as the manufacture of complicated castings in metal casting industry. In this paper, the flow behavior of sand particles in the core box was investigated synchronously with transparent core box, high-speed camera, and pressure measuring system. The flow pattern of sand particles in the shooting head of the core shooting machine was reproduced with various colored core sand layers. Taking both kinetic and frictional stress into account, a kinetic-frictional constitutive correlation was established to describe the internal momentum transfer in the solid phase. Two-fluid model (TFM) simulations with turbulence model were then performed and good agreement was achieved between the experimental and simulation results on the flow behavior of sand particles in both the shooting head and the core box. Based on the experimental and simulation results, the flow behavior of sand particles in the core box, the formation of “dead zone” in the shooting head, and the effect of drag force were analyzed in terms of sand volume fraction (αs), sand velocity (Vs), and pressure variation (P).